Determine the Treatment Outcomes of Severe Acute Malnutrition in Pediatric Population by Using Formula F100 Therapeutic Feed - Sajid Hussain Sherazi, Sadaf Liaqat, Rabia Nisar, Maria Khalid, Rebeya Hashim (Pakistan Journal of Medical & Health Sciences, 2024)
Objective: To determine the prevalence and treatment outcomes of severe acute malnutrition in children. Study Design: Prospective study Place & Duration of Study: Department of Paediatrics, Niazi Welfare Foundation Teaching Hospital,Sargodha from 1st July 2019 to 31st December 2019. Methodology: One hundred and fifty patients of both genders presented with severe acute malnutrition were included. Patient’s ages were ranging from 2 months to 48 months. Patient’s demographics including age, sex, malnutrition type and address were recorded after taking informed consent from patient’s parents/guardians. Presentations on admission were recorded. F75 and F100 therapeutic feed were given to all the patients (WHO Guideline for malnutrition). Outcomes were recorded. Results: There were 80 (53.33%) male patients while 70 (46.67%) were females. Sixty eight(45.33%) patients were of age less than 10 months and 82 (54.67%) were of age above 10 months. From 150 patients, 134 (89.33%) patients were marasmus and 16 (10.67%) patients were kwashiorkor. Mean weight gain by using F100 was 7.26±3.45 gm/kg/day. 92% patients were recovered and 8% died during treatment. The most common presentation was diarrhea. Conclusion: The use of F75 and F100 therapeutic feed for the treatment of severe acute malnutrition was very effective with low rate of mortality. Keywords: Severe acute malnutrition (SAM), Pediatric population, F75, F100 Feed, Treatment, Outcomes